Toxic and antinutritional substances content of Amaranthus dubius Mart. ex Thell. Effect of plant part and harvesting season - Molina, Edgar; González-Redondo, Pedro; Moreno-Rojas, Rafael; Montero-Quintero, Keyla; Ferrer, Rosa; Sánchez-Urdaneta, Adriana Beatriz (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2016)
Amaranth species are gaining increasing interest for human and animal nutrition, although its use is limited due to their toxic and antinutritional substances contents. The contents of toxic and antinutritionals substances (oxalates, phytates, total phenols, condensate tannins, hydrolysable tannins and cyanide) in the leaves, stems, and panicles of Amaranthus dubius Mart. ex Thell., not yet investigated, were evaluated in both rainy and dry seasons. The plants were cultivated in El Néctar Hacienda, located in Merecure, in the municipality of Acevedo, Miranda State, Venezuela (10Âº31”™38" N, 66Âº33”™16" W). The concentration of oxalates, phytates, total phenols, condensate and hydrolysable tannins were determined by classic colorimetric techniques, the cyanide being determined by silver nitrate titration. The content of toxic and antinutrients in A. dubiusranged from 169.6 to 368.5 mg of oxalates.kg-1 DM, 0.771 to 7.482 mg of phytates.g-1DM, 0.47 to 1.77 mg of total phenols.g-1DM, and 0.22 to 1.20 mg of condensate tannins.g-1DM. Cyanide and hydrolysable tannins were not detected. The values of most of these substances presented differences according to harvesting seasons and plant part (P<0.001), as well as an interaction between both factors. The content of toxic and antinutrients was generally higher in the dry than in the rainy season for all parts of the plant. The harvesting season and the plant part affect the content of toxic and antinutritional substances in A.dubius, whose values were, however, below the maximum levels allowed by regulators for human consumption. Therefore, as raw material it does not need to be processed in order to guarantee its harmlessness.